On the taxonomic status of two giant cockroaches of Bionoblatta (Blattodea, Blaberidae) collected by José Pinto da Fonseca, a founder of the Brazilian Society of Entomology - Leonardo Polizeli; Ângelo Parise Pinto (Journal of Orthoptera Research)
The blaberids Parahormetica hylaeceps Miranda-Ribeiro, 1936 and Bion mastrucatus Rehn, 1937 were described in the 1930s from single males collected by José Pinto da Fonseca (JPF) in the 1910s. Both specimens came from the region of Mariana municipality, Minas Gerais State, an ecotonal formation between the Atlantic Forest and Cerrado domains in southeastern Brazil. Recently, P. hylaeceps was transferred to Bionoblatta Rehn, 1940, and its strong morphological similarity with Bion mastrucatus (already in Bionoblatta) was highlighted, indicating the need to investigate the validity of these names. Here, we addressed this question by analyzing photos of the type material, comparing original descriptions, and examining data on both the collecting site and the collector’s history. We conclude that Parahormetica hylaeceps should be considered a senior synonym of Bion mastrucatus syn. nov.; hence, the valid name should be Bionoblatta hylaeceps (Miranda-Ribeiro, 1936). We also provide a new diagnosis, synonymy, and review of the distribution of this species, finding Bionoblatta hylaeceps to be endemic to the Itacolomi Peak region. We also present a short account of the work of JPF, including his relevance to Brazilian entomology and itinerary for collecting these specimens. Bionoblatta have five poorly known species of blaberids that, despite recent advances in the genus taxonomy, are still pending review.